Lasègue and his sign - JMS Pearce (Advances in Clinical Neuroscience & Rehabilitation)
In the diagnosis of the almost ubiquitous low back pain, with or without sciatic nerve radiation, there are few reliable physical signs. Restricted straight leg raising (SLR) is one of the most useful signs that indicates a lesion of the sciatic nerve roots by stretching, irritation or entrapment in or adjacent to the intervertebral foramen. Though commonly labelled Lasègue’s sign, Lasègue did not describe it in his published papers.